Architectural Element Analysis of Channel Deposits in The Cipamingkis River Section, Jatiluhur Formation - Gani, Reza Moh. Ganjar; Girabie, Ludwi; Revanda, Naufal Fajar; Sunarie, Cecep Yandri; Pahlevi, Raihan Shaib; Rahayu, Dewi Sri (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Architectural element analysis on the channel has been held with the length of the object study more than 3 kilometers in the Cipamingkis River Jatiluhur Formation. The channel deposit and association of the channel are generally influenced by the turbidity system in the slope setting. The determination of architectural elements in this study must consider the stratigraphic record, characterized by facies, facies association, internal geometry, and bounding surface. The study area has seven lithofacies and must be grouped into three facies associations. Channel elements are generally filled with coarse-grained sediment material and show amalgamation, thickened beds, and gradation of sandstone. There is fine-grained material that was found, such as siltstone, which indicates a levee element that has an older stratigraphic position than the channel element. Four-channel elements can be distinguished based on the characteristics of the constituent materials and their internal geometry. The vertical stack creates a channel complex in the study area, with channel element evolution starting from incision, and the last phase is aggradation-migration.